Early Echocardiographic Findings of Pulmonary Hypertension-specific Therapy in Children - Akif KAVGACI; Fatma Sedef TUNAOGLU; Serdar KULA; Ayse Deniz OGUZ; Semiha TERLEMEZ; Fatma INCEDERE (Medeniyet Medical Journal)
Objective: Echocardiography is a very useful tool for the diagnosis and evaluation of pulmonary hypertension (PH). This study was planned to investigate whether echocardiographic (ECHO) data of patients with PH are effective in the follow-up and course of treatment. Methods: A retrospective analysis of the data from 26 PH patients was performed. Analyses were performed on the data of the patients, including their demographics and ECHO findings. The ECHO measurements of the patients were labeled as 0 (beginning of the PH specific therapy), 1 (on the 15th day of the therapy), 2 (one month after the previous echocardiogram). Results: The left ventricle ejection fraction (EF) (p=0.05) and fractional shortening (FS) (p=0.038) values in ECHO2 were significantly higher than those in ECHO1. Aortic velocity-time integral1 (VTI1) was significantly higher than aortic VTI0 (p=0.001; p<0.01), and tricuspid annular plane systolic excursion2 (TAPSE2) was significantly higher than TAPSE0 (p=0.046). Moreover, right ventricular ejection time1 (RVET1) was significantly higher than RVET0 (p=0.034), and left ventricular ejection time1 (LVET1) was significantly higher than LVET0 (p=0.003). Conclusions: This study provides information on ECHO parameters that improve during the initial stages of therapy. Based on the results of our study, even at the beginning of treatment, there were increases in right and left ventricular filling, EF, and FS. Clinical deterioration of PH can be detected early/before the clinical status of the patient worsens with detailed examinations using echocardiography.